A Study on Parents' Attitude Towards Current Practices of Primary Schools in Manipur - Kiranmala, Rajkumari; Singh, S. Birahari; Devi, R.K. Lilapati; Singh, R.K. Surseh (Voices of Teachers and Teacher Educators, 2023)
he study investigates parents' attitude towards specific aspects of primary schools like the school policies, curriculum and teachers, etc. Testing the significant difference in attitudes of parents towards the practices of primary schools was the major aim of the study. The study consists of 341 parents selected in multistage random sampling. 37-item attitude instruments were used to collect responses. The overall parents' attitude towards the current practices of primary schools in Manipur, in both private and government schools, are perceived as highly favourable. Parents in both government and private schools report not practicing hands-on activities at school. They express a desire of being informed by schools about daily affairs and development. The study highlights the insignificant difference in the parents' attitude towards practices of primary schools, from which it can be inferred that there is no actual support for the assertion that private schools are always better than government schools. In certain aspects, private school parents have comparatively higher positive attitude than parents of Government schools to some extent